2003
DOI: 10.1063/1.1534381
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and crystallization kinetics in HfO2 thin films grown by atomic layer deposition

Abstract: We report the effects of annealing on the morphology and crystallization kinetics for the high-gate dielectric replacement candidate hafnium oxide (HfO 2 ). HfO 2 films were grown by atomic layer deposition ͑ALD͒ on thermal and chemical SiO 2 underlayers. High-sensitivity x-ray diffractometry shows that the as-deposited ALD HfO 2 films on thermal oxide are polycrystalline, containing both monoclinic and either tetragonal or orthorhombic phases with an average grain size of ϳ8.0 nm. Transmission electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(62 citation statements)
references
References 23 publications
3
56
0
3
Order By: Relevance
“…Non-combinatorial studies of HfO 2 (Ref. 45) and the HfO 2 -Al 2 O 3 (Ref. 46) system are in agreement with the basic finding of cubic and monoclinic phases, and the fact that Al 2 O 3 addition stabilizes the amorphous phase.…”
Section: Advanced Gate Stack Materialssupporting
confidence: 59%
See 1 more Smart Citation
“…Non-combinatorial studies of HfO 2 (Ref. 45) and the HfO 2 -Al 2 O 3 (Ref. 46) system are in agreement with the basic finding of cubic and monoclinic phases, and the fact that Al 2 O 3 addition stabilizes the amorphous phase.…”
Section: Advanced Gate Stack Materialssupporting
confidence: 59%
“…They found that the conductivities of a series of ternary alloys along the line Mn 0. 45 Further research used PLD to deposit CCS libraries of Nb-Sn-Ti-O. 214 Their results showed that films with Sn levels less than 20 at% maintained low resistivity and high transparency, while reducing the refractivity of the coating (a reduction in the refractivity reduces the effective path length of light through a material, thus reducing the probability of absorption).…”
Section: Other Tco Systemsmentioning
confidence: 99%
“…As can be seen, distinct diffraction peaks can be observed, and these diffraction peaks are ascribed to the monoclinic phase of HfO 2 [12]. A peak ascribed to either tetragonal or orthorhombic HfO 2 , often appearing at 2θ=30.3°in HfO 2 films deposited by atomic layer deposition and sputtering [13][14][15][16], was not detected in this study. The HfO 2 films, therefore, mainly crystallized in the monoclinic phase without the tetragonal or orthorhombic phase.…”
Section: Crystalline Phases Of Hfo 2 Filmsmentioning
confidence: 58%
“…As can be seen, distinct diffraction peaks can be observed, and these diffraction peaks are ascribed to the monoclinic phase of HfO 2 [13]. A peak ascribed to either tetragonal or orthorhombic HfO 2 , often appearing at 2y ¼ 30:31 in HfO 2 films deposited by ALD and sputtering [14][15][16][17], was not detected in this study. The HfO 2 films, therefore, mainly crystallized in the monoclinic phase without the tetragonal or orthorhombic phase.…”
Section: Crystalline Phases Of Hfo 2 Filmsmentioning
confidence: 64%